Crescimento facial vertical após a adenotonsilectomia em respiradoresorais: O que esperamos é o que encontramos? - Bernardo Quiroga Souki (2009)
Introduction: The association between nasal impairment and dentofacial morphology has been studied for more than a century. Controversies still exist about this subject, despite a lot of information is available on the literature. Therefore, the purpose of this PhD thesis was to evaluate if expectations meet reality regarding some assumptions previously established on clinicians minds. Three points were investigated: 1) epidemiological report on the prevalence of malocclusion among a group of children consecutively admitted at a referral mouth breathing (ENT) center, studying the association of such malocclusionsand upper airway obstructive factors, 2) the impact of respiration normalization on vertical dentofacial growth during two stages of dental development after adeno-/tonsillectomy (T&A) and 3) the impact of respiration normalization on vertical dentofacial growth after adeno-/ tonsillectomy (T&A), controlling the results with a matched group of untreated mouth breathing children. Methods: The work described in this thesis consists of three papers. Each one answering each objective listed above. The first paper reports a cross-sectional, descriptive study, carried out at an Outpatient Clinic for Mouth-Breathers. Dental inter-arch relationships and nasal obstructive variables of 401 children were diagnosed and the appropriate cross tabulations were done. In the second paper, linear and angular cephalometric measurements, as well as superimposing tracings of serial lateral cephalograms of 39 patients in the treatment group were compared with those of 31 untreated mouth breathing controls. Cephalometric records in the treatment group comprised registrations made at baseline before surgery (T0), and then at approximately 1 year postoperatively (T1). Corresponding registrations were available for the control group, with baseline cephalometric radiographs taken approximately 1 year before the second one (T0 and T1, respectively). Treated and untreated individuals were divided into deciduous and mixed dentition groups to aid identification of an optimum timing for normalizing the respiration after T&A, under a vertical dentofacial perspective. In the third paper the impact of T&A onthe vertical dentofacial growth is revisited after an untreated group of mouth breathing children served as controls. Results: Paper #1 - Mean age was 6 years and 6 months (SD: 2y7m), ranging from 2 to 12 years. All subjects were evaluated by otorhinolaryngologists to confirm mouth breathing habit. Adenoid/tonsil obstruction was detected in 71.8% of this sample, regardless of the presence of rhinitis. Allergic rhinitis alone was found in 18.7% of the children. Non obstructive mouth breathing wasdiagnosed in 9.5% of this sample. Posterior crossbite was detected in almost 30% of the children during primary and mixed dentitions and 48% in permanent dentition. During mixed and permanent dentitions, anterior open bite and class II malocclusion were highly prevalent. More than 50% of the mouth breathing children carried a normal inter-arch relationship in the sagital, transversal and vertical planes. Univariate analysis showed no significant association betweenthe type of the obstruction (adenoids/tonsils obstructive hyperplasia or the presence of allergic rhinitis) and malocclusions (class II, anterior open bite and posterior crossbite). Paper #2 - After one year of follow up, no statistically significant difference on vertical dentofacial growth was observed in deciduous or mixed dentitions treatment groups compared to same stage untreated control groups. The reduction of the divergence (NL-MP) between maxilla and mandible was statistically significant greater for adeno-/tonsillectomy group during primary dentition. Paper #3 - Statistically significant growth (p<0.000) was found for all linear measurements (SBL-Go, SBL-Me, NL-Me) in both groups (TG and CG). Areduction in LAFH/TAFH, SBL-MP and NL-MP, as well as an increase inPFH/TAFH, were the growth mean behavior both in TG and CG. There was no statistically significant difference between TG and CG regarding the mandibular rotation.Conclusions: . The prealence of posterior crossbite is higher in mouth-breathing childrenthan in the general population. During mixed and permanent dentitions, anterior open bite and class II malocclusion were more likely to be present in mouth breathers. Although more children showed these malocclusions, most mouth breathing children evaluated in this study did not match the expected mouth breathing dental stereotype. . In this population of mouth breathing children, the obstructive size of adenoids or tonsils and the presence of rhinitis were not risk factors to the development of class II malocclusion, anterior open bite or posterior crossbite. . Regarding the vertical dentofacial growth pattern, normalization of the mode of respiration after T&A in young children (deciduous dentition) is not moreeffective than in older children (mixed dentition). The normalization of the mode of respiration, after T&A, did not change the pattern of mandibular vertical growth, after one year, when compared to a matched untreated group of mouth breathers. Apparently, there is a greater clockwise rotation of the anterior portion of maxilla in adeno-/tonsillectomized children than in obstructed controls during primary dentition. . The previously posted concept that T&A improve the vertical dentofacialgrowth must be revisited.